Levantamiento geoquímico regional de la hoja Liberia 1:200.000 (Costa Rica) - Marín Guzmán, Fernando (2011)
A regional geochemical survey was performed on the Liberia 1:200.000 topo-graphic map, based on the collection of 221 staram sediment samples, at a mean density of one sample per 30 km2. The analysis was made by atomic absorption and the results processed by programs of the G-EXEC system, to perform raw-data and statistically smoothed maps of the regional geochemical landscape. Lisefulness of the methodology employed to discern between different geochemical domians due to geology, mineralization on pollution is concluded, in view of the important spatial associations of Cu, Zn - Fe -Ag - Pb and Co - Ni found. Accomplishment of the Geochemical Atlas of Costa Rica, at a scale 1:200,000, is thus outlined.